Northwest History. Alaska. Floods & Flood Control. (1937)
Town Of Nenana Flooded Again: Ice-Chocked Tanana River Sends Water Through Streets. TOWN OF NENANA FLOODED AGAIN Ice-Choked Tanana River Sends Water Through Streets. FAIRBANKS, Alaska, May 18. (/P)~Ice-choked Tanana river sent its second flood in two days pouring through the town of Nenana, 50 miles southwest of here, today but at last reports the river was dropping slowly. Radio and telephone reports from Nenana said the new flood reached the 14-foot crest of the ope which inundated the railroad ana steamboat shipping center of less than 1000 population yesterday. Residents, already driven from their homes, were believed to be in no immediate danger. Schools were closed. In the east end of town the water was four feet deep. The only places not under water were the Alaska railroad's station and the center part of Main street. Water entered the Episcopal mission property and threatened the Northern Commercial company's warehouse and hundreds of tons of freight in other warehouses. Ice Is Running Out. A great run. of ice passed down the Tenana during the day, but this was said to be clearing. Ice held on some of the Yukon river's tributaries, though warm weather hastened the break-up time. The ice was intact at Manley Hot Springs on the Tanana and at Tanana station and Nulato on the Yukon, reports reaching here said. Fort Yukon, a trading post 150 miles to the northeast, was partly under water. The flood, which came when Yukon ice broke, was reported by radiophone to be subsiding. At Fairbanks the Chena river was normal and schools, used by refugees during the recent flood, reopened today.